Selective Manipulation of Discrete Mannosidase Activities in the Endoplasmic Reticulum by Using Reciprocally Selective Inhibitors. (4th May 2017) - Kuribara, Taiki; Hirano, Makoto; Speciale, Gaetano; Williams, Spencer J.; Ito, Yukishige; Totani, Kiichiro
Abstract: Within the endoplasmic reticulum, immature glycoproteins are sorted into secretion and degradation pathways through the sequential trimming of mannose residues from Man9 GlcNAc2 to Man5 GlcNAc2 by the combined actions of assorted α‐1, 2‐mannosidases. It has been speculated that specific glycoforms encode signals for secretion and degradation. However, it is unclear whether the specific signal glycoforms are produced by random mannosidase action or are produced regioselectively in a sequenced manner by specific α‐1, 2‐mannosidases. Here, we report the identification of a set of selective mannosidase inhibitors and development of conditions for their use that enable production of distinct pools of Man8 GlcNAc2 isomers from a structurally defined synthetic Man9 GlcNAc2 substrate in an endoplasmic reticulum fraction. Glycan processing analysis with these inhibitors provides the first biochemical evidence for selective production of the signal glycoforms contributing to traffic control in glycoprotein quality control. Abstract : New traffic controllers : We report the discovery of a set of selective mannosidase inhibitors, exemplified by deoxymannojirimycin and deoxynojirimycin, and conditions for their use. Glycan processing analysis with these inhibitors provided biochemical evidence for regioselective production of signal glycoforms contributing to traffic control in glycoprotein quality control.